The fugitive was patent foramen ovale - Anjali Deepa; Aritra Mukherji; Raghu Prasad Shridharagadda; Ravi Kishore Ganga Amancharla (IHJ Cardiovascular Case Reports, 2023)
A Patent Foramen Ovale (PFO) with paradoxical right to left shunt is a well-known culprit for conditions like cryptogenic stroke, migraine and de-compression sickness. Till date, there is scanty data on the relationship between right to left PFO shunt and vertigo. Our case highlights the importance of high level of suspicion for coexistence of paradoxically shunting PFO in patients with unexplained dizziness and paroxysmal vertigo.